Gestão de suprimentos no setor público: análise das práticas de intralogística do município de Caicó/RN - Santos, Aline Oliveira dos (2023)
The present study aims to analyze the management of intralogistics regarding the practices of receipt, storage and distribution of physical supplies in the municipal government of Caicó/RN. The work is justified by the search for administrative efficiency in the various management processes that need to be constantly improved by the State. Intralogistics management has repercussions on the final activities of institutions, where a step in its practices can impact transport in the continued provision of public services. It is a case study, descriptive and with a qualitative approach, whose unit of analysis is the intralogistics management practices institutionalized in the Department of Material and Heritage of the Municipality of Caicó The collection took place through field research, with the help of interviews and interviews , non-participant observation and documentary research. The research participants were the servants directly involved in the intralogistics activities of materials in the municipality. Data analysis took place via content analysis with triangulation of data collected from different sources. The results showed that the main bottlenecks for supply interruption are in the receiving, distribution and distribution stages, with emphasis on supply entry activities and lack of application of information management. Thus, practices were suggested aimed at improving the processes found